1996
DOI: 10.1071/rd9960167
|View full text |Cite
|
Sign up to set email alerts
|

Fetal insulin-like growth factor (IGF)-I and IGF-II are regulated differently by glucose or insulin in the sheep fetus

Abstract: We investigated the effect of restoration of normoglycaemia or normoinsulinaemia in fetuses of starved ewes on plasma IGF-I and IGF-II concentrations. Paired maternal and fetal blood samples were taken during an initial 2-day control period, after 48 h of maternal starvation, during 24 h fetal infusion of glucose (n = 6) or insulin (n = 4) while maintaining maternal starvation and after 48 h maternal refeeding. After 48 h starvation maternal and fetal plasma IGF-I, insulin and blood glucose fell (maternal IGF-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(45 citation statements)
references
References 0 publications
2
43
0
Order By: Relevance
“…Previous studies have suggested that fetal IGF-I and IGF-II are independently regulated in sheep fetal circulation and show a different expression pattern (Fowden and Silver, 1995;Oliver et al, 1996). Expression of the IGF-I and IGF-II genes depend on the origin of the cells and their development stage (Wang et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that fetal IGF-I and IGF-II are independently regulated in sheep fetal circulation and show a different expression pattern (Fowden and Silver, 1995;Oliver et al, 1996). Expression of the IGF-I and IGF-II genes depend on the origin of the cells and their development stage (Wang et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The major hormones regulating foetal growth in late gestation appear to be insulin and IGFs (Fowden, 1989;Harding et al, 1993), which regulate foetal nutrient uptake and the distribution of nutrients in the foetus. In turn, they are regulated by foetal nutrient supplies (Oliver et al, , 1996. Therefore, reducing the glucose supply to the foetus decreases circulating insulin and IGF concentrations and, consequently, reduces foetal growth.…”
Section: Foetal Growthmentioning
confidence: 99%
“…However, it seems unlikely that such a large reduction in weight would not be accompanied by functional impairment. Both the fetal and postnatal kidney express GH and IGF-receptors (Feld & Hirschberg 1996, Oliver et al 1996 and postnatally, kidney growth and function is very sensitive to circulating GH. Compensatory renal growth after unilateral nephrectomy (Flyvbjerg et al 1999b) and renal hypertrophy in diabetes (Flyvbjerg et al 1999a) has been shown to be GH dependent and acromegaly and GH therapy are associated with increased glomerular filtration rate and renal plasma flow in man (Ogle et al 1992).…”
Section: Igf-i Concentrations In the Fetusmentioning
confidence: 99%